Population behavior of Macaca fascicularis: An analysis of environmental and social interactions shaping in the Terawang Cave habitat, Central Java - Riyani, Siti Rosidah; Hernawati, Diana; Chaidir, Diki Muhamad (Inornatus: Biology Education Journal, 2025)
This study aims to identify and analyze the behavior of the population of Long-Tailed Macaque (LTM) in Terawang Cave and to evaluate the influence of environmental factors in the form of temperature, humidity, and light intensity on these behavioral variations At the research location, there were three groups of LTMs, but the sample was the group closest to the cave of 10 individuals. %. LTM behavior is measured using quantitative surveys and scan sampling methods. Observations were made on 6 LTM behaviors and three climatic data (temperature, humidity, and light intensity) in the Terawang Cave environment. There are six types of behavior: mating behavior at 1.87%, agonistic behavior at 10.13%, affiliative behavior at 14.76%, playing behavior at 17.89%, resting behavior at 21.05%, and ingestion behavior at 34.30%.  The higher the temperature in the Terawang Cave environment, the lower the LTM activity. The higher the humidity, the higher the MEP activity. Meanwhile, MEP behavior activity increased at medium light intensity. The Canonical Correspondence Analysis (CCA) shows that temperature, humidity, and light intensity influence macaque behavior, with higher temperatures increasing resting, mating activity is more common in humid conditions, playing more in lower light, and ingestion depending on light intensity. In contrast, affiliating behavior is mainly driven by social interactions, highlighting the impact of environmental factors and human activities on macaques, which is essential for conservation efforts.